2021
DOI: 10.1101/2021.07.30.454402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structures of SARS-CoV-2 B.1.351 neutralizing antibodies provide insights into cocktail design against concerning variants

Abstract: The spread of the SARS-CoV-2 variants could seriously dampen the global effort to tackle the COVID-19 pandemic. Recently, we investigated the humoral antibody responses of SARS-CoV-2 convalescent patients and vaccinees towards circulating variants, and identified a panel of monoclonal antibodies (mAbs) that could efficiently neutralize the B.1.351 (Beta) variant. Here we investigate how these mAbs target the B.1.351 spike protein using cryo-electron microscopy. In particular, we show that two superpotent mAbs,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These mAbs were chosen because they had appreciable activity against the initial Omicron variant. Among these antibodies, 20 were directed to the class 1 to class 4 epitope clusters on the RBD (Barnes et al, 2020): S2K146 (Park et al, 2022), Omi-3 (Nutalai et al, 2022), Omi-18 (Nutalai et al, 2022), BD-515 (Cao et al, 2021), XGv051 (Wang et al, 2022b), XGv347 (Wang et al, 2022a), ZCB11 (Zhou et al, 2022), COV2-2196 (tixagevimab) (Zost et al, 2020), LY-CoV1404 (bebtelovimab, authorized to treat COVID-19) (Westendorf et al, 2022), XGv289 (Wang et al, 2022a), XGv264 (Wang et al, 2022b), S309 (sotrovimab) (Pinto et al, 2020), P2G3 (Fenwick et al, 2022), SP1-77 (Luo et al, 2022), BD55-5840 (Cao et al, 2022), XGv282 (Wang et al, 2022a), BD-804 (Du et al, 2021), 35B5 (Wang et al, 2022g), COV2-2130 (cilgavimab) (Zost et al, 2020), and 10-40 (Liu et al, 2022a). The other three were non-RBD mAbs, with C1520 (Wang et al, 2022h) targeting the NTD, C1717 (Wang et al, 2022h) targeting NTD-SD2, and S3H3 (Hong et al, 2022) targeting SD1.…”
Section: Resultsmentioning
confidence: 99%
“…These mAbs were chosen because they had appreciable activity against the initial Omicron variant. Among these antibodies, 20 were directed to the class 1 to class 4 epitope clusters on the RBD (Barnes et al, 2020): S2K146 (Park et al, 2022), Omi-3 (Nutalai et al, 2022), Omi-18 (Nutalai et al, 2022), BD-515 (Cao et al, 2021), XGv051 (Wang et al, 2022b), XGv347 (Wang et al, 2022a), ZCB11 (Zhou et al, 2022), COV2-2196 (tixagevimab) (Zost et al, 2020), LY-CoV1404 (bebtelovimab, authorized to treat COVID-19) (Westendorf et al, 2022), XGv289 (Wang et al, 2022a), XGv264 (Wang et al, 2022b), S309 (sotrovimab) (Pinto et al, 2020), P2G3 (Fenwick et al, 2022), SP1-77 (Luo et al, 2022), BD55-5840 (Cao et al, 2022), XGv282 (Wang et al, 2022a), BD-804 (Du et al, 2021), 35B5 (Wang et al, 2022g), COV2-2130 (cilgavimab) (Zost et al, 2020), and 10-40 (Liu et al, 2022a). The other three were non-RBD mAbs, with C1520 (Wang et al, 2022h) targeting the NTD, C1717 (Wang et al, 2022h) targeting NTD-SD2, and S3H3 (Hong et al, 2022) targeting SD1.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of additional antibodies are also in competition for bids with ACE2. Before the emergence of the omicron variant, previous studies showed that a large number of antibodies were still effectively neutralizing SARS-CoV-2 variants [31]. However, recent findings indicate that 85% of previously described neutralizing antibodies are no longer effective against the novel omicron Variant [32].…”
Section: Rbd-ace2 Protein Dockinmentioning
confidence: 99%
“…Samples for cryo-EM study were prepared essentially as described 15,52 (Supplementary Table 4). All EM grids were evacuated for 2 min and glow-discharged for 30 s using a plasma cleaner (Harrick PDC-32G-2).…”
Section: Cryo-em Data Collection Processing and Structure Buildingmentioning
confidence: 99%